Embalming mom : essays in life - Burroway, Janet (Sightline books., 2002)
Janet Burroway followed in the footsteps of Sylvia Plath. Like Plath, she was an early Mademoiselle guest editor in New York, an Ivy League and Cambridge student, an aspiring poet-playwright-novelist in the period before feminism existed, a woman who struggled with her generation's conflicting demands of work and love. Unlike Plath, Janet Burroway survived.